Respuestas

2012-06-01T11:56:00+02:00

4x-2(3+2x)=3(3-x)

4x-6-4x=9-3x

2x-6=9-3x

2x+3x=9+6

5x=15

x=3

-x/2+1-2x/3=-2

-x/2-2x/3-1=-2

-x/2-2x/3=-2+1

-7x/3=-1

7x/3=1

x=3/7

  • Usuario de Brainly
2012-06-01T15:02:03+02:00

a)

 

4x - 2(3 + 2x) = 3(3 - x)

4x - 6 - 4x = 9 - 3x

- 6 = 9 - 3x

-6 - 9 = -3x

-15 = -3x

-15/-3 = x

5 = x ....R/.

 

b)

-x/2 + 1 - 2x/3 = -2

-x/2 - 2x/3 = -2 - 1

(-3x- 4x)/6 = -3

-7x = (-3)(6)

-7x = -18

x = -18/-7

x = 18/7... R/.

 

Espero haberte podido ayudar